Prevalence of type 1 and type 2 diabetes in children and adolescents in Germany from 2002 to 2020: A study based on electronic health record data from the DPV registry. Issue 12 (14th December 2022) - Stahl‐Pehe, Anna; Kamrath, Clemens; Prinz, Nicole; Kapellen, Thomas; Menzel, Ulrike; Kordonouri, Olga; Schwab, K. Otfried; Bechtold‐Dalla Pozza, Susanne; Rosenbauer, Joachim; Holl, Reinhard W.
Abstract: Background: To provide estimates of the nationwide prevalence of type 1 diabetes (T1D) and type 2 diabetes (T2D) in individuals younger than 20 years of age in Germany from 2002 to 2020 and to identify trends. Methods: Data were obtained from the electronic health record "Diabetes Prospective Follow‐up Registry (DPV)" specific to diabetes care. Prevalence was estimated based on prevalent cases at the end of each year for the years 2002, 2008, 2014, and 2020 per 100 000 persons assuming a Poisson distribution and directly age‐ and/or sex‐standardized to the population in 2020. Individuals younger than 20 years of age with a clinical diagnosis of T1D or 10–19‐year‐olds with T2D were eligible for inclusion in the study. Results: The standardized T1D prevalence per 100 000 persons was 138.9 (95% CI: 137.1; 140.6) in 2002 and 245.6 (243.1; 248.0) in 2020. The standardized T2D prevalence per 100 000 persons was 3.4 (3.1; 3.8) in 2002 and 10.8 (10.1; 11.5) in 2020. The annual percent change (APC) in prevalence declined over the three periods 2002–2008/2008–2014/2014–2020 (T1D: 6.3% [3.6%; 9.0%]/3.1% [0.7%; 5.5%]/0.5% [−1.7%; 2.85], T2D: 12.3% [5.3%; 20.8%]/4.7% [−0.6%; 10.3%]/3.0% [−1.8%; 8.0%]). From 2014 to 2020, the highest APCs were observed among 15–19‐year‐olds (T1D: 2.5% [1.3%; 3.6%], T2D: 3.4% [−0.5%; 7.5%]). Conclusions: The increase in diabetes prevalence has slowed, but medical care should be prepared for an increase in adolescents with diabetes. Abstract : Highlights The prevalence rates of type 1 diabetes and type 2 diabetes in Germany are higher than estimated by the International Diabetes Federation (IDF). Since 2014, prevalence rates have increased only in 15–19‐year‐olds. 摘要: 研究背景:评估2002 2020年德国20岁以下人群中1型糖尿病(T1D)和2型糖尿病(T2D)的患病率, 并确定其趋势。 方法:数据来源于糖尿病前瞻性随访登记系统(Diabetes Prospective Follow‐up Registry, DPV)。根据2002年、2008年、2014年和2020年每10万人年末发病例数, 采用Poisson分布和直接对2020年人群进行年龄和(或)性别标化, 估算患病率。小于20岁临床诊断为T1D的患者或10 19岁的T2D患者符合纳入标准。 结果:在2020年, 标化T1D患病率为138.9 / 10万(95% CI: 137.1;140.6)和245.6 (243.1;248.0), 标化T2D患病率为3.4/10万 (3.1;3.8)和10.8 (10.1;11.5)。2002‐2008年/ 2008‐2014年/ 2014‐2020年3个时期患病率的年度变化百分比(APC)均呈下降趋势(T1D: 6.3% (3.6%;9.0%) / 3.1% (0.7%;5.5%) / 0.5% (‐1.7%;2.85)、T2d:12.3% (5.3%;20.8%) / 4.7% (‐0.6%;10.3%) / 3.0% (‐1.8%;8.0%))。2014‐2020年, 15 19岁人群APC最高(T1D: 2.5% (1.3%;3.6%), T2D: 3.4% (‐0.5%;7.5%))。 结论:青少年糖尿病患病率的增长速度有所减缓, 但应做好医疗保健准备。